ERGONOMIC RISK LEVEL ANALYSIS USING NORDIC BODY MAP (NBM), RULA, AND REBA METHODS ON MURYA 2 COLLECTION TAILORS - Novia Ramadhani Widya Prasetyo; Anik Dwiastuti; Rudi Nurdiansyah; Abdul Muid; Muhammad Nursyamsu Alhafidh; Rafida Salwa Nida; Zahra Aulia Fitri (RADJA PUBLIKA, 2026)
This study aims to analyze ergonomic risk levels among sewing workers at Murya 2 Collection using the Nordic Body Map (NBM), Rapid Upper Limb Assessment (RULA), and Rapid Entire Body Assessment (REBA). This study used a descriptive design with an observational ergonomics approach. The subjects were six active sewing workers, and data were collected through NBM questionnaires, direct observation, photographic documentation, and interviews. NBM was used to identify subjective musculoskeletal complaints, while RULA and REBA were applied to assess objective postural risks during sewing activities. The results showed that the highest complaints occurred in the upper back, neck, lower neck, right shoulder, middle back, lower back, right wrist, right hand, and right foot sole. Based on total NBM scores, two workers were categorized as high risk, while four workers were categorized as moderate risk. RULA results showed that most workers were in the medium-high risk category, whereas REBA results indicated that all workers were in the medium risk category. The use of the three methods showed that dominant complaints were generally consistent with postural risk findings. Recommended improvements include scheduled microbreaks, targeted stretching, posture awareness, foot relaxation, and simple workstation adjustments suitable for SME conditions.